Microstructure and Thermoelectric Properties of N-type 95%Bi2Te3-5%Bi2Se3 Compound Prepared by High Energy Milling and Hot Extrusion - Kim, Hyo-Seob; Hong, Soon-Jik (Current Nanoscience, 2014)
Nanocrystalline n-type 95%Bi2Te3-5%Bi2Se3 bulk with prepared by the combined application of high energy milling and hot extrusion processes in this study. The effect of milling time on the microstructure of powders was characterized by scanning electron microscopy (SEM). With increasing milling time, powder size quickly decreased, and finally yielded nanocrystalline Bi2Te3 of less than 200nm grain size and of spherical morphology, at 90min. Microstructure and thermoelectric properties of the samples after hot-extrusion were also investigated. The hot-extruded samples observed fine-grains and improved mechanical properties. The maximum power factor of the nanaocrystalline Bi2Te3 bulk sample reaches 4.6x10-5W/mK2 at room temperature, which is lower than the zone-melted one due to high impurity and oxidization.
Keywords: Microstructure